Persia and its pople - Sykes, Ella C. (Routledge Library Editions: Iran., 2012)
This volume gives a popular description of Iran and was the result of the author's extensive travelling in the country and close knowledge of its people and customs over a period of 3 years at the turn of the nineteenth century.